Comparison of Endometriosis Characteristics in Adolescents and Women of Advanced Reproductive Age - Ottowgeissler Yabes Melaneson Paiki; Marta Isyana Dewi; Ali Budi Harsono (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
ABSTRACT Objective: To compare clinical and pathological characteristics of endometriosis between adolescents (10–19 years) and women of advanced reproductive age (35–45 years) to guide early diagnosis and tailored management. Methods: A retrospective, cross-sectional study of 68 patients (31 adolescents; 37 advanced-age women) with laparoscopically and histopathologically confirmed endometriosis at Dr. Margono Soekarjo Regional General Hospital between January 2022 and December 2024. Statistical analyses included independent t-tests, chi-square tests, and multivariate logistic regression. Results: Adolescents exhibited higher dysmenorrhea prevalence (80.6% vs. 43.2%; p=0.003), more early-stage disease (Stage I–II: 71% vs. 22%; p